2015
DOI: 10.1039/c5cc04256a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast fluorescence spectroscopy reveals a dominant weakly-emissive population of fibril bound thioflavin-T

Abstract: In this communication, using sub-picosecond resolved fluorescence upconversion spectroscopy, we discover that despite a large fluorescence enhancement observed for thioflavin-T in insulin fibrils, the majority of fibril bound thioflavin-T undergoes efficient ultrafast conformational relaxation, and thus does not contribute to the characteristic fluorescence enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 26 publications
4
71
1
Order By: Relevance
“…The binding constants thus estimated from the fitting, were found to be 1.0 10 6 and 4.1 10 4 m À1 .E arlier,T hT was reported to follow two modes of binding, one in the fibrillar channel and the other in the grooves of the fibrillars urface. [42][43][44] Due to structural complementarity between ThT and the fibrillar channel, the binding in the inner channel of the fibrils is very strong compared to that on the surface. Considering the similar chemical structure of ThT and 2Me-DABT,i na nalogy,w ea lso propose that the stronger binding mode corresponds to the 2Me-DABT bound to the inner channel of the fibril and the weaker mode is due to the binding of 2Me-DABT ontot he fibrillar surface.…”
Section: Resultsmentioning
confidence: 99%
“…The binding constants thus estimated from the fitting, were found to be 1.0 10 6 and 4.1 10 4 m À1 .E arlier,T hT was reported to follow two modes of binding, one in the fibrillar channel and the other in the grooves of the fibrillars urface. [42][43][44] Due to structural complementarity between ThT and the fibrillar channel, the binding in the inner channel of the fibrils is very strong compared to that on the surface. Considering the similar chemical structure of ThT and 2Me-DABT,i na nalogy,w ea lso propose that the stronger binding mode corresponds to the 2Me-DABT bound to the inner channel of the fibril and the weaker mode is due to the binding of 2Me-DABT ontot he fibrillar surface.…”
Section: Resultsmentioning
confidence: 99%
“…A combination of molecular dynamics and site-specific mutation studies using b-sheet forming peptides revealed that ThT binds to the surface ridges of the b-sheets, interacting particularly with hydrophobic residues across !4 b-strands ( Figure 6, left panel). These tight hydrophobic interactions hinder inter-ring rotation and LE to TICT state conversion of ThT [32,33,98,99]. Tight binding may also stabilize ThT's positive charge in a twisted conformation.…”
Section: Tht Binding To Amyloid Fibrilsmentioning
confidence: 99%
“…However, this type of binding is the minority option. The major binding mode is in fact via electrostatic interactions with the positive charge on ThT ( Figure 6, right panel), which allows formation of the TICT state with consequent low fluorescence yields [99]. The existence of more than one type of ThT binding site is a salutary reminder that a fibril's change in ThT fluorescence intensity does not necessarily mean a change in the fibril concentration, but could simply arise from a shift in the equilibrium between two ThT binding sites on a given fibril surface.…”
Section: Tht Binding To Amyloid Fibrilsmentioning
confidence: 99%
“…According to our spectrofluorometric analysis, free ThT molecules exhibited a weak fluorescence between 460 and 550 nm upon excitation at 420 nm (Figure c), which is attributed to the rapid quenching of the excited state by nonradiative conformational relaxation in a free form. In contrast, we observed a strong fluorescence from the ThT‐bound insulin nanofibrils; the enhanced ThT fluorescence should be caused by the restriction of conformational relaxation around the central CC bond in its excited electronic state . The fluorescence intensity of ThT increased with the increasing length of insulin fibrils (Figure S4, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%